The Use of Anagram Technique to Improve Student’s Vocabulary Mastery in SMPN 04 Dedai - Wulandari, Widya (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The objective of this research is to describe the students’ improvement in vocabulary mastery and the students’ participation in learning activities through the implementation of Anagram techniques. This research was carried out due to the students having low motivation in learning. Besides, they had trouble mastering and memorizing the vocabulary, so they had poor vocabulary. Therefore, the researcher decided to use the Anagram technique to overcome the problem in this class. In this research, classroom action research (CAR) was used as the research design; both qualitative and quantitative methods were used to analyze the data. The researcher used a vocabulary test and observation to collect the data. The tools of data collection techniques are observation checklists, grading papers, and field notes. The findings showed that there is an improvement in the students’ vocabulary mastery and students’ participation in learning activities through the implementation of the Anagram technique in the classroom. In cycle one, the mean score of students’ vocabulary mastery was 72,3 and in cycle two it was 86,7. The student’s participation in learning activities was also improved; in cycle one, it was 62.96%, while in cycle two, it was 92.85%. It could be concluded that the Anagram technique could improve the students’ vocabulary mastery and the students’ participation in learning activities, especially for seventh-grade students of SMPN 04 Dedai.